2017
DOI: 10.1158/2159-8290.cd-16-1032
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Identity in AML Depends on Disruption of Nonpromoter Regulatory Elements and Is Affected by Antagonistic Effects of Mutations in Epigenetic Modifiers

Abstract: We performed cytosine methylation sequencing on genetically diverse AML patients and found leukemic DNA methylation patterning is primarily driven by non-promoter regulatory elements and CpG shores. Enhancers displayed stronger differential methylation than promoters, consisting predominantly of hypomethylation. AMLs with dominant hypermethylation featured greater epigenetic disruption of promoters, while those with dominant hypomethylation displayed greater disruption of distal and intronic regions. Mutations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
142
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(160 citation statements)
references
References 47 publications
15
142
1
Order By: Relevance
“…However, despite the wide variety of molecular aberrations observed, clustering of large AML cohorts based on global transcriptomic or epigenomic data generally reveals only a small number of clusters. 19,66,238,240,255 This may reflect the fact that although the large transcriptional networks in eukaryotic cells have many theoretical states, only a small number of these are stable and accessible. What is also becoming clearer is that leukemic transcriptional networks are highly plastic, and emerging data suggest that in addition to being implicated in leukemogenesis alterations to transcriptional networks may play a role in AML progression, resistance, and relapse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite the wide variety of molecular aberrations observed, clustering of large AML cohorts based on global transcriptomic or epigenomic data generally reveals only a small number of clusters. 19,66,238,240,255 This may reflect the fact that although the large transcriptional networks in eukaryotic cells have many theoretical states, only a small number of these are stable and accessible. What is also becoming clearer is that leukemic transcriptional networks are highly plastic, and emerging data suggest that in addition to being implicated in leukemogenesis alterations to transcriptional networks may play a role in AML progression, resistance, and relapse.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model, loss of TET2 can cooperate with Flt3 ‐ITD mutations to remodel DNA methylation, including at the Gata 2 locus with concomitant reduction in Gata 2 mRNA expression, and increased methylation at the GATA2 locus is also observed in AML with mutated TET2 and FLT3 ‐ITD . Furthermore, a high‐resolution study of genome‐wide cytosine methylation changes found AML‐specific changes in methylation associated with active HSC enhancers, but not at promoters . Clustering based on genome‐wide methylation patterns in primary AML samples reflected known molecular defects, suggesting that individual molecular aberrations, including mutations in IDH and DNMT3A , lead to specific changes in DNA methylation .…”
Section: Global Alterations In Chromatin Organizationmentioning
confidence: 95%
See 1 more Smart Citation
“…Next we aimed to compare global DNA methylation patterns from AML patients carrying the R882H mutation with AML patients not containing it. Glass et al (2017) reported enhanced reduced representation bisulfite sequencing (ERRBS) DNA methylation profiles of 119 AML samples, 27 of them with R882H mutation (Glass et al, 2017). The data include CpGs covered between 10-400x, methylation changes were called requiring at least 3 samples to support the difference.…”
Section: Correlation Of Aml Patient Dna Methylation Profiles With Thementioning
confidence: 99%
“…Based on our current unprecedented progress in describing the genetic and epigenetic landscape of AML, we know that aberrant differentiation is frequently, at least in part, driven by epigenetic deregulation. 5,6 Examples include mutations in genes involved in DNA methylation and modification of histone marks. Mutations in IDH2 are observed in 10% to 12% of patients with AML, while another 10% of patients carry mutations in the related IDH1 gene.…”
mentioning
confidence: 99%